Level and Predictors of Minimum Dietary Diversity Among Pregnant Women in Eastern Ethiopia: Evidence From Facility-Based Cross-sectional Survey - Esayas Kassahun MPH; Firehiwot Mesfin PhD; Tefera Kasahun Ali MSc; Lemma Getacher MPH (SAGE Publishing, 2023)
Low dietary diversity is one of the most serious public health issues in developing countries, resulting in poor nutritional status, particularly vitamin and mineral deficiencies in pregnant women. However, there is insufficient information on the current status of pregnant women's minimum dietary diversity in Eastern Ethiopia. The main aim of this study is to assess the level and predictors of minimum dietary diversity among pregnant women in Harar Town, Eastern Ethiopia. The study was conducted on 471 women using a health institution-based cross-sectional study design from January to March 2018. A systematic random sampling method was used to select the study participants. A pretested and structured questionnaire was used to collect data on the minimum dietary diversity. A logistic regression model was used to assess the relationship between the outcome variable and the independent variables. A P -value of .05 was used to indicate statistical significance. The proportion of pregnant women who had adequate minimum dietary diversity was 52.7% (95% CI: (47.9%, 57.6)). Urban residence [(AOR = 0.08, 95% CI: (0.02, 0.33)], smaller family size [(AOR = 7.28, 95% CI: (3.25, 16.28)], husband occupation [(AOR = 2.55, 95% CI: (1.39, 4.6)], husband support [(AOR = 3.85; 95% CI: (1.23, 12.02)], having more than 1 dwelling room [(AOR = 5.7, 95% CI: (2.32, 13.8) and medium wealth quantile [AOR = 1.93, 95% CI: (1.13.39)] were associated with adequate minimum dietary diversity. The level of minimum dietary diversity was low in the study area. It was linked to urban residency, smaller family sizes, husband employment, husband support, having more than 1 bedroom, and medium wealth quantile. Efforts should be made to improve husband support, wealth index, husband occupation, and food security status in order to boost mothers' minimal dietary diversity.